Education for patients with rheumatoid arthritis: Is it worth it? (2003)
Rheumatoid arthritis (RA) is the most frequent chronic inflammatory disease affecting approximately 1% of the white population, particularly females (3 times more often than males) (1). Because of its articular and extraarticular manifestations and complications, such as infections and osteoporosis, RA has a considerable impact on a patient's quality of life, with mayor physical, psychological, and social consequences. Treatment of RA includes not only medications but also education and cognitive?behavioral interventions (2). Recently, Riemsma et al described the impact of the use of education as a therapeutic tool in patients with RA (3). These authors proposed a categorization of educational practices into information only, counseling, and behavioral therapy. This approach is important because it emphasizes the various types of educational systems and allows analysis of data more objectively to avoid comparisons of unrelated interventions.